Implement, improve and expand your statewide longitudinal data system : creating a culture of data in education - McQuiggan, Jamie; Sapp, Armistead W. (Hoboken : John Wiley and Sons, Inc., 2014)
"Step-by-step guidance for implementing an effective statewide longitudinal data systemEvery U.S. state faces challenges in its efforts to ensure the highest-quality education for students. To address these challenges, a growing number of states are establishing statewide longitudinal data systems (SLDSs), a data-rich system integrating relevant data about a student's education. Implementing Statewide Longitudinal Data Systems for Education presents a detailed and contextualized discussion of SLDSs, which will serve as a recipe for states that want to implement an SLDS, develop design and enactment of new and existing SLDS systems, addressing implementation, operation and optimization. Provides a contextualized discussion of the history and purpose of SLDSs Describes how to plan for and implement an SLDS, including best practices regarding data governance, standards and privacy Discusses proven methods of data management, and details the two most popular methods of database architectures used for SLDSs Provides 5 case studies of states successfully using SLDSs Offers suggestions for expansion and inclusion of new datasets over time This essential book addresses the culture of data concept, providing a guide for states to usher in a new era in their education system where data is invaluable and used by everyone, not simply the newest version of the old system. A robust LDS initiative includes linked student records, teacher records, test scores, course selection, finances, certifications, licensure, salary and more. Concluding with a discussion of the potential future uses of SLDS, this book is the ultimate guide to SLDS implementation and understanding"--
Michigan's SLDS: Moving Beyond Compliance The System; Involving Stakeholders: Shared Goals, Shared Responsibility; Engineered to Last: Roll with the Changes; The Approach: Start with the Basics and Expand; Career and College Ready Initiative: How Longitudinal Data Can Inform the Discussion; Conclusion; Notes; Chapter 7 North Carolina Case Study: New SLDS, Existing Partnerships; Stakeholders and the NC P20W System; Running Start: A History of Collaboration; The Vision; State Legislation Reinforcing SLDS; Looking Ahead; Conclusion; Notes; Chapter 8 Sharing Information with Others.
Machine generated contents note: Preface Acknowledgments Chapter 1: How to Establish a Successful SLDS What is a Statewide Longitudinal Data System? What an SLDS can do that Sneaker Net cannot What it takes to implement (or improve) a successful SLDS Preview Notes Chapter 2: The SLDS Landscape History of longitudinal data systems The State of SLDSs Today Data Management Models Conclusion Notes Chapter 3: Getting Started on your SLDS SLDS Planning & Preparation Establish a Data Governance Board Address Interoperability of the data Set policies for Data Security and Student Privacy Evaluate Current Systems and Make Connections Make it Sustainable Conclusion Notes Chapter 4: Data Management: Creating One Version of the Truth What is Master Data Management? Incorporating MDM Principles in your SLDS Conclusion Notes Chapter 5 Florida Case Study: The Up and Downside of Being the First Florida's SLDS Renovating what exists using Federal grants Conclusion Notes Chapter 6 Michigan's SLDS: A Tool for Reinventing the Economy Michigan's SLDS: Moving Beyond Compliance Career & College Ready Initiative: how longitudinal data can inform the discussion Conclusion Notes Chapter 7 North Carolina Case Study Stakeholders and the NC P20W system The Vision State Legislation reinforcing SLDS Conclusion Notes Chapter 8: Sharing Information with Others Public Information Sharing: What information is the public entitled to and interested in? Policymakers and state-level decision makers: How can legislators enable and use longitudinal data? Researchers: How can states leverage researchers to make the longitudinal data answer key questions? Establishing the Connection with Academia Parents: What do parents need to have access to in an SLDS, and how will it make a difference? Students: How can an SLDS provide students with more intuitive, instant access to their own student record? Conclusion Notes Chapter 9: Using Data in Schools and Classrooms Teachers Administrators The Teacher-Student Record Link Conclusion Notes Chapter 10: Expanding your SLDS: Adding Out of School Time and Health Care Data Collective Impact: the longitudinal data connection OST: What happens when they're not in school? Health Care Data How to facilitate collective impact initiatives Conclusion Notes Chapter 11: A Culture of Data: Using longitudinal data to solve big problems Creating a Culture of Data Data Driven Decision Tools Response to Intervention (RTI) Early Warning Systems Conclusion Notes Chapter 12: It's Not About the Data Ways to Sustain the System Conclusion Notes About the Author(s) Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher;.
Keywords: Educational statistics -- Computer programs; Longitudinal method -- Data processing; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Electronic books; Electronic books